Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapter 5 Review Problem Set - Page 231: 35



Work Step by Step

RECALL: The distributive property states that for any real numbers a, b, and c: $a(b+c) = ab+ac \\a(b-c) = ab - ac$ Use the distributive property (which is shown above) to obtain: $=x(x^2-x+6)-2(x^2-x+6) \\=x(x^2)+x(-x) +x(6)-2(x^2) -2(-x) -2(6) \\=x^3-x^2+6x-2x^2+2x-12$ Combine like terms to obtain: $=x^3 + (-x^2-2x^2)+(6x+2x)-12 \\=x^3+(-3x^2)+8x-12 \\=x^3-3x^2+8x-12$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.